2020
DOI: 10.34117/bjdv6n5-073
|View full text |Cite
|
Sign up to set email alerts
|

Mapeamento e análise espectro-temporal das unidades de conservação de proteção integral da administração federal no bioma caatinga

Abstract: Mapeamento e análise espectro-temporal das unidades de conservação de proteção integral da administração federal no bioma caatinga Spectro-temporal mapping and analysis of integral protection conservation units of federal administration in the caatinga biome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 1 publication
0
15
0
4
Order By: Relevance
“…The scenic beauty of the area is intensely harnessed by the growing tourism industry mainly in the Xingó region. There are also other economic activities of great ecological impact in the region, such as the cultivation of fish in net-tanks, as well as social conflicts caused by invasions of protected areas within the protected area (UC) carried out by members of the labor movement-earth MST (Freire et al, 2019).…”
Section: Environmental Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…The scenic beauty of the area is intensely harnessed by the growing tourism industry mainly in the Xingó region. There are also other economic activities of great ecological impact in the region, such as the cultivation of fish in net-tanks, as well as social conflicts caused by invasions of protected areas within the protected area (UC) carried out by members of the labor movement-earth MST (Freire et al, 2019).…”
Section: Environmental Degradationmentioning
confidence: 99%
“…Given these aggravating factors, we highlight the presence of several Integral Protection Conservation Units, in which one of the most prominent is called "São Francisco River Natural Monument", also known as Mona do San Francisco, which is located completely inserted into the Caatinga biome. The San Francisco River Natural Monument is characterized, above all, by the exuberant water mirror of the Xingó Hydroelectric Power Plant lake, belonging to the San Francisco Hydroelectric Company-CHESF, and its surroundings formed by rocky walls, covered by Caatinga vegetation (Freire et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although this CU presents a legal mechanism for its conservation and is defined by the SNUC (National System of Conservation Units) as an integral protection unit, the presence of families that live in the region is perceived (Azevedo and Bernard, 2015), as well as the presence of indigenous groups, agricultural production, livestock and ecotourism (Freire, 2013). A recently published research, Freire et al (2017), reveals that from 14 conservation units (CU's) of integral protection of the Caatinga biome examined, Parna Catimbau is one of the CU's with the highest environmental degradation index. The authors concluded that, in addition to the socioenvironmental conflicts between farmers, squatters, indigenous populations and managers of ICMBIo (Chico Mendes Institute for Biodiversity Conservation), there were significant losses of caatinga physiognomies, especially in areas with rock vegetation in areas with natural wall of sandstone -typical from this CU and with difficult access.…”
Section: Introductionmentioning
confidence: 99%
“…This article was elaborated by virtue of results obtained in the inter-institutional research Joaquim Nabuco Foundation and Federal University of Campina Grande entitled "Mapping and Spectro-Temporal Analysis of Conservation Units of Integral Protection of the Caatinga Biome of the Federal Administration" (Freire et al, 2017), carried out between 2013 and 2016, as well as the contents of the course "Remote Sensing and Environmental Monitoring". Ministered at the Integrated Center for Georeferenced Studies for Social Research Mário Lacerda de Melo (CIEG/ FUNDAJ, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…São dados importantes, pois a continuidade da elevação da temperatura superficial nas áreas de caatingas poderá Com as medidas de classe pôde-se obter a representação em extensão de áreas em km², assim o intervalo entre 0,131 a 0,170 (cor bege) representam na sua maior parte solos expostos degradados com vegetação herbácea esparsa. Essas áreas no ano de 1995 correspondiam a 315,26 km², no ano de 2006 essas áreas ocupavam 186,98 km² e em ) mostra a paisagem no alto do sítio Chapadão, na formação arenítica dos paredões do catimbau, na imagem é possível perceber em algumas áreas dos paredões ausência de vegetações rupestres Freire (2015),. já relacionava os impactos das mudanças climáticas com a sustentabilidade da vegetação rupestre da caatinga, pois essa Parque Nacional é de posse e domínio público, sendo que as áreas particulares incluídas em seus limites serão desapropriadas, de acordo com o que dispõe a lei".Contudo, essa situação mostra a fragilidade do gerenciamento dessa unidade de conservação, sendo necessário um replanejamento no plano de gestão do Parna do Catimbau alinhados com a SNUC…”
unclassified